Evaluation of the outcome of interferon therapy in chronic hepatitis B infection - Rahmet ÇAYLAN; Kemalettin AYDIN; İftihar KÖKSAL and Recep ÖKSÜZ and Uğur KOSTAKOĞLU and Ümit ÇOBANOĞLU and Nurucihan ARI and Sevim AYDIN (Turkish Journal of Gastroenterology, 2019)
-